2009
DOI: 10.1016/j.pec.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Patient–provider communication and perspectives on smoking cessation and relapse in the oncology setting

Abstract: Objective-To fill a gap in research by examining cancer patient-provider communication regarding tobacco use and patients' perspectives regarding their experiences with smoking cessation and relapse.Methods-In-depth interviews were conducted with 20 lung and head and neck cancer patients and 11 health care providers.Results-Qualitative analyses revealed that cancer patients express high levels of motivation to quit smoking; however patients do not ask providers for assistance with quitting and maintaining abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 18 publications
2
85
0
Order By: Relevance
“…This finding is in line with our previous formative work suggesting that providers do not feel qualified to provide smoking cessation assistance and prefer to refer patients to other resources [10]. Other frequently cited barriers by providers include feeling unable to help the patient to quit, patient resistance and time constraints [10,16]. Together, these data support the need for greater training for healthcare providers to increase knowledge of evidence-based smoking cessation interventions, and to enhance awareness that patients with cancer are motivated to quit smoking and that providers can make an impact with brief interventions (i.e., lasting <3 min).…”
Section: Are the Clinical Practice Guidelines Currently Being Implemesupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in line with our previous formative work suggesting that providers do not feel qualified to provide smoking cessation assistance and prefer to refer patients to other resources [10]. Other frequently cited barriers by providers include feeling unable to help the patient to quit, patient resistance and time constraints [10,16]. Together, these data support the need for greater training for healthcare providers to increase knowledge of evidence-based smoking cessation interventions, and to enhance awareness that patients with cancer are motivated to quit smoking and that providers can make an impact with brief interventions (i.e., lasting <3 min).…”
Section: Are the Clinical Practice Guidelines Currently Being Implemesupporting
confidence: 91%
“…For example, a survey completed by Warren and colleagues with lung cancer physicians found that only 33% felt adequately trained to provide cessation interventions [16]. This finding is in line with our previous formative work suggesting that providers do not feel qualified to provide smoking cessation assistance and prefer to refer patients to other resources [10]. Other frequently cited barriers by providers include feeling unable to help the patient to quit, patient resistance and time constraints [10,16].…”
Section: Are the Clinical Practice Guidelines Currently Being Implemesupporting
confidence: 61%
See 1 more Smart Citation
“…In a qualitative study of 20 lung and head and neck cancer patients and 11 health care providers, Simmons et al (2009) found that while many of the patients were interested in quitting, they did not ask for help, and providers were inconsistent in the type of smoking cessation information and help offered . In another study of cancer survivors (n = 1,825), only 81% of providers knew of their smoking status, and only 72.2% of current smokers (n = 310) were advised to quit smoking, missing that teachable moment (Coups, Dhingra, Heckman, & Manne, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, despite these new guidelines, half of comprehensive cancer centers do not have tobacco treatment programs [90]. Lung cancer patients generally do not receive tobacco treatment from their oncology providers, nor is smoking routinely addressed in the primary care setting following diagnosis [52,[91][92][93]. Consequently, most lung cancer patients who smoke have not used established behavioral and pharmacological tobacco treatment [48], and a lack of patient-provider communication in the context of smoking and a lung cancer diagnosis might exacerbate this gap in treatment.…”
Section: Lung Cancer Patients Particularly Blacks Are a Vulnerable mentioning
confidence: 99%